Theios Sophistes : essays on Flavius Philostratus' Vita Apollonii - Demoen, Kristoffel.; Praet, Danny, 1968- (Mnemosyne, Supplements, 2009)
Flavius Philostratus' Life of Apollonius of Tyana (Vita Apollonii), written in the first half of the third century CE, is a key text in the cultural, literary and religious history of the Second Sophistic and of Late Antiquity. Its generic and formal diversity, its shifting cultural and historical background, as well as its protean hero, call for a multifaceted and interdisciplinary reading. Theios Sophistès is the first collection of interpretative essays on the Vita Apollonii . Leading scholars in the field and younger critics make for a combination of methodological continuity and innovation. The book is divided into two sections, one focusing on literary and philological discussions and relating the Vita to other ancient texts and genres, and one dealing with religious and philosophical aspects. The wide range of approaches and perspectives does justice to the high level of literary, historical and philosophical-religious sophistication of this text.